(untitled) (Polis (Santiago), 2018)
This is the chapter 16th of his monumental work titled Retrying Galileo, 1633-1992, published in the 2005 by the University of Californian Press, Berkeley. This book is an examination of Galileo’s affair from the moment of the sentence of the toscano scientist by the Inquisition (Santo Oficio) in 1633, to its supposed rehabilitation by Pope John Paul II in 1992. Its approach is in subjects such as: if the sentence was just, and if it would prove the mutual incompatibility between science and religion; it puts emphasis in the texts that constitute the primary sources, and of which emerge the historical facts and the different controversial subjects. In chapter 17 of the same study of professor Finocchiaro, a precise evaluation is contained, realistic and balanced, of the efforts of Pope John Paul II to up to date the Church’s position in Galileo’s case, along with a negative estimation both of the papal commission in charge of his reexamination, us of its president, Cardinal Paul Pourpard. The translation was made by Hermes H. Benítez, and has been specifically authorized by the publishing house